16 An Analysis of the Impact of Establishing an Ambulatory Stroke Team. (16th September 2019) - Menagh, Colin; Wilson, David; Dynan, Kevin; Power, Michael; Hull, Karen; McCallion, Charlotte; Matthews, Maureen
Abstract: Background: The South Eastern Trust established an Ambulatory Stroke Team (AST) in October 2017. This consisted of Stroke Nurses and a Specialty doctor with Stroke consultant support. During the initial pilot the AST team worked Monday – Friday 9-5pm. The majority of assessments took place in the emergency department. The overall aims were to improve length of stay for TIAs / stroke mimics and improve the percentage of strokes being admitted directly to the Stroke Unit. Methods: Using quality improvement methodology we worked through several Plan, Do, Study, Act (PDSA) cycles. The most significant intervention was the introduction of a protected direct to stroke unit bed. A database was kept of all patients seen, including final diagnoses and patients discharged after assessment, preventing admission and saving bed days. Results: A 6 month period was analysed from April to September 2018. 312 patients were reviewed - 159 (51%) stroke mimics, 108 (35%) strokes and 45 (14%) TIAs. 54 patients were identified for early discharge and appropriate follow-up. Bed days saved was estimated at 110 days. Direct to stroke unit percentage improved from 30% in October 2017 when the AST was introduced to 82% in January 2019. Conclusion: A dedicated Ambulatory Stroke Team can prevent hospital admissions and save bed days due to rapid identification and specialist assessment of suspected TIAs and strokes. Multidisciplinary team working as part of a quality improvement project can improve the percentage of strokes admitted directly to the stroke unit.